VICARIOUS TRAUMA PADA RELAWAN BENCANA ALAM - Nur Halimah, Siti; Listyanti Widuri, Erlina (HUMANITAS (Jurnal Psikologi Indonesia), 2012)
The purpose of this study was to determine the symptoms of vicarioustrauma and its impact in the lives of volunteers, the factors that causevicarious trauma and expectations for volunteers and government agencies.This study used qualitative research method based on phenomenology asit can reveal the meaning of an event. Based on the analysis result throughinterviews and observation, showed that volunteers who returned fromduty experience vicarious trauma as a result of interaction with multipletrauma victims. There are two main factors causing the occurrence ofvicarious trauma on volunteers are internal factors and external factors.Internal factors include the characteristics (personality) and adversity thatare owned by volunteers and how they performance it. External factorsare type of victim, the social environment and work climate with all kindsof problems.